Recurrence of Anti-Semaphorin 3B–Mediated Membranous Nephropathy after Kidney Transplantation. Issue 3 (March 2022) - Fila, Marc; Debiec, Hanna; Perrochia, Hélène; Djouadi, Nabila; Verpont, Marie-Christine; Buob, David; Ronco, Pierre
Significance Statement: We report the first case of early recurrence after transplantation of membranous nephropathy associated with antibodies directed at semaphorin 3B, a recently described putative antigen. This case provides strong evidence that the disease is caused by anti-semaphorin 3B antibodies entering the graft from the recipient circulation. It also suggests that these antibodies are a new biomarker of the disease that should be carefully monitored before and after transplantation. Finally, the finding supports the efficacy of rituximab. Abstract : Background: Membranous nephropathy (MN) is rare in pediatric patients, although its diagnosis may be underestimated in children who are responsive to corticosteroid therapy prescribed for a suspicion of minimal change disease. It is most often associated with an autoimmune disease, predominantly lupus. We previously reported the occurrence of early-onset MN associated with semaphorin 3B in nine children and two adults. Methods: Biopsies were performed on native kidney and at 1 and 5 months after transplantation. Semaphorin 3B antigen was detected in immune deposits by immunohistochemistry and confocal microscopy on paraffin-embedded biopsies. Anti-semaphorin antibodies were detected by Western blot and analyzed sequentially. Results: We report the first case of early recurrence after transplantation in a 7-year-old boy who presented with severe nephrotic syndrome and advanced kidney failure. There was no evidence of hereditary or associated autoimmune disease. Abundant, almost coalescent deposits were seen by electron microscopy and bright granular, subepithelial staining was observed for semaphorin 3B antigen. Western blot analysis of serum revealed anti-semaphorin 3B antibodies. Recurrence of MN occurred 25 days after transplantation and manifested as nephrotic range proteinuria despite conventional immunosuppressive therapy. Kidney biopsies confirmed histologic MN recurrence with colocalization of semaphorin 3B antigen and IgG. The patient was treated with rituximab. Anti-semaphorin 3B antibodies, which were detected at transplantation, were not detected 40 days after rituximab. Conclusion: This case provides evidence that anti-semaphorin 3B antibodies are pathogenic and should be monitored in patients with MN.